Optimization of Biodiesel Production From Bakul Oil - Ferdous, Mohammad Kaniz; Uddin, M Rahim; Uddin, M Rakib; Khan, Maksudur R; Islam, MA (Journal of Chemical Engineering, 2017)
In this paper, biodiesel production from Bakul oil (Mimusops Elengi) by three-step method and optimization were studied by the application of factorial design. Bakul Oil (BO) was extracted from Bakul seeds by press method and soxhlet extraction method. Bakul seed was collected from the local sources. The raw oil, containing 11.1 wt% Free Fatty Acid (FFA) and viscosity was 76.62 mm2/s. Because of higher FFA content of BO transesterification method cant be applied, so three-step method was conducted for biodiesel production and optimization. In the three-step method, the first step was saponification of the oil followed by acidification to produce FFA and finally esterification of FFA to produce biodiesel. The reaction parameters in saponification, acidification and esterification reaction were optimized. Silica gel was used during esterification reaction to adsorb water produced in the reaction and silica gel to FFA ratio was 1:10 wt/wt. Hence the reaction rate was increased and finally the FFA was reduced to 0.70 wt%. A factorial design was studied for esterification reaction and developed to obtain the higher yield of biodiesel. Finally various properties of biodiesel such as FFA, viscosity, specific gravity, cetane index, pour point, flash point were measured and compared with biodiesel and petro-diesel standard. Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 14-18